2020
DOI: 10.1155/2020/1419520
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Efficacy and Safety of Phosphodiesterase Type 5 Inhibitors with Tamsulosin for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia with or without Erectile Dysfunction: A Network Meta‐Analysis

Abstract: Purpose. The purpose of this study was to compare the relative safety and efficacy of different types of phosphodiesterase type 5 inhibitors (PDE5-Is) with tamsulosin for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostate hyperplasia (BPH) (BPH-LUTS) with or without erectile dysfunction (ED). Methods. We use the Stata version 13.0 to conduct the network meta-analysis (NMA) with a random effects model of the Bayesian framework. The International Prostate Symptom Score (IPSS), Maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The order of drug administration does not have any significant effects [ 17 ]. A meta-analysis suggests that sildenafil–tamsulosin is a reliable combination therapy for men with LUTS with/without ED [ 18 ]. Further studies are required to compare tadalafil vs sildenafil in combination with tamsulosin on LUTS improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The order of drug administration does not have any significant effects [ 17 ]. A meta-analysis suggests that sildenafil–tamsulosin is a reliable combination therapy for men with LUTS with/without ED [ 18 ]. Further studies are required to compare tadalafil vs sildenafil in combination with tamsulosin on LUTS improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Men with detrusor hyperactivity respond better to combination treatment with α-blocker with an anticholinergic rather than monotherapy [ 7 ]. Combination treatment also makes use of PDE5 inhibitors (even in the absence of erectile dysfunction)[ 8 ] and 5 ARIs for larger gland sizes. Nevertheless, a significant proportion of these patients do not respond to the first-line medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous meta-analysis comparing combination therapy with α-blockers and PDE5Is with monotherapy suggested that combination therapy improved LUTS. [ 7 ] Previous NMAs [ 29 , 30 ] comparing phosphodiesterase type 5 inhibitors combined with tamsulosin among the general population suggested that sildenafil combined with tamsulosin is superior to other administrations. In our study, however, sildenafil (25 mg) combined with α-blockers is not proven to be superior to other administrations.…”
Section: Discussionmentioning
confidence: 99%